1998
DOI: 10.1038/28867
|View full text |Cite|
|
Sign up to set email alerts
|

Role of HIF-1α in hypoxia-mediated apoptosis, cell proliferation and tumour angiogenesis

Abstract: As a result of deprivation of oxygen (hypoxia) and nutrients, the growth and viability of cells is reduced. Hypoxia-inducible factor (HIF)-1alpha helps to restore oxygen homeostasis by inducing glycolysis, erythropoiesis and angiogenesis. Here we show that hypoxia and hypoglycaemia reduce proliferation and increase apoptosis in wild-type (HIF-1alpha+/+) embryonic stem (ES) cells, but not in ES cells with inactivated HIF-1alpha genes (HIF-1alpha-/-); however, a deficiency of HIF-1alpha does not affect apoptosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

50
1,589
6
18

Year Published

1998
1998
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 2,307 publications
(1,692 citation statements)
references
References 25 publications
50
1,589
6
18
Order By: Relevance
“…These adoptive responses during hypoxia contribute to the aggressive behavior of many cancers and are largely mediated by HIF-1, the major transcription factor activated during hypoxia (Semenza, 2000(Semenza, , 2003Harris, 2002). Although HIF-1 usually participates in adoptive responses to hypoxia to promote tumor cell growth and survival, a possible role of HIF-1 in regulation of apoptosis has also been discussed (Carmeliet et al, 1998) …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These adoptive responses during hypoxia contribute to the aggressive behavior of many cancers and are largely mediated by HIF-1, the major transcription factor activated during hypoxia (Semenza, 2000(Semenza, , 2003Harris, 2002). Although HIF-1 usually participates in adoptive responses to hypoxia to promote tumor cell growth and survival, a possible role of HIF-1 in regulation of apoptosis has also been discussed (Carmeliet et al, 1998) …”
Section: Discussionmentioning
confidence: 99%
“…Hif-1a promotes cell death through an increase in p53 or other proapoptotic proteins such as Bcl-2/E1B 19 kDa interacting protein 3 (BNIP3) or BNIP3L (NIX) (Carmeliet et al, 1998;Bruick, 2000;Guo et al, 2001;Sowter et al, 2001). Under most circumstances however, Hif-1a promotes survival of cancer or endothelial cells under hypoxic condition and also protects against apoptosis induced by serum deprivation or by anticancer agents (Alvarez-Tejado, 2001; Sasabe et al, 2005;Piret et al, 2004;Kim et al, 2004a, b;Zhang et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…2 Hypoxia results in stabilization of HIF-1a, facilitating nuclear HIF-1a binding and restoration of oxygen homeostasis by inducing glycolysis and angiogenesis through upregulation of vascular endothelial growth factor (VEGF). 3 Experimental and clinical evidence suggest that the hypoxic fraction in solid tumors reduces sensitivity to conventional treatment modalities, influences growth and may increase malignant progression. 3,4 Importantly, hypoxia has been clinically demonstrated to predict an adverse treatment outcome in the radiotherapeutic management of cancer of the head and neck, uterine cervix and soft tissue sarcomas.…”
mentioning
confidence: 99%
“…Therefore, we initially hypothesized that the ROSscavenging and iron-chelating potential of MCGA3 may play a role in the p21 induction by providing a hypoxic condition. Recent studies (Carmeliet et al, 1998;Abeysinghe et al, 2001;Goda et al, 2003) have shown that HIF-1a-involved p21 transcriptional activation without p53 transcriptional function. Our p21-promoter assays clearly reflect the p53-independent, Sp1-dependent transcriptional activation of p21 by MCGA3.…”
Section: Discussionmentioning
confidence: 99%
“…MCGA3 upregulates p21 as well as overcomes UVA-mediated early decrease of p21 Hypoxia not only induces angiogenesis and promotes cell growth and survival in cancer cells but also leads to growth arrest and apoptosis (Carmeliet et al, 1998;Goda et al, 2003;Greijer and van der Wall, 2004). Recently, hypoxia-mediated cell cycle arrest and induction of apoptosis has been shown to be regulated by p21 activation (Bossenmeyer-Pourie et al, 2002).…”
Section: Mcga3 Inhibits Uva-initiated Survival Signalsmentioning
confidence: 99%